Activated carbon surface modification by catalytic chemical vapor deposition of natural gas for enhancing adsorption of greenhouse gases. Issue 3 (June 2019) - Rezvani, Hadi; Fatemi, Shohreh; Tamnanloo, Javad
Graphical abstract: Abstract: Activated Carbon (AC) was modified by Catalytic Chemical Vapor Deposition (CCVD) of Urban Natural Gas (UNG) using microwave irradiation. Pretreatment of the as-prepared activated carbon was performed by washing with nitric acid and Ni impregnation by nickel nitrate solution (with 1.5–3.5 wt.% Ni/AC) followed by N2 thermal treatment at 450 °C. Modification of the AC surface was carried out by carbon source flow through the surface under microwave irradiation. Carbon nanofibers (CNFs) growth was observed on the surface of AC by FESEM analysis. The properties of the surface were characterized by FTIR, FESEM, EDX and BET analysis. The effect of the carbon source and the content of Ni/AC were investigated on the CNF quality. Among three carbon sources (pure methane, methane-ethane mixture, and UNG), the fibers formed under UNG flow possessed the best surface characteristics. Presence of Ni improved the rate of nanofiber formation at lower temperatures and shortened the run time. It was observed that specific surface area and total pore volume of the modified AC increased by 12% and 41% after CNF growth, respectively. Pore volume distribution indicated a slight reduction of the micropores while the number of mesopores increased with fiber formation. Equilibrium adsorption experiments were conducted on the samples for CO2, CH4, CO, and H2 . The adsorption capacity and selectivity of the greenhouse gases have been improved up to 15% and 60%, respectively, whereas hydrogen adsorption capacity was negligible and remained unchanged after surface modification.